CDK4/6 inhibitors have potent activity in combination with pathway selective therapeutic agents in models of pancreatic cancer - Franco, Jorge (Impact Journals LLC, 2014)
Pancreatic ductal adenocarcinoma (PDA) has a poor prognosis, in part, due to the therapy-recalcitrant nature of the disease. Loss of the CDK4/6 inhibitor CDKN2A is a signature genetic event in PDA. Therefore, PDA may be amenable to treatment with pharmaceutical CDK4/6 inhibitors. Surprisingly, response to CDK4/6 inhibition was highly variable in PDA models, and associated with differential suppression of gene expression. Mitotic genes were repressed and FOXM1 was uniformly attenuated; however, genes involved in DNA replication were uniquely suppressed in sensitive models. Aberrant induction of Cyclin E1 was associated with resistance, and knockdown demonstrated synergistic suppression of the cell cycle with CDK4/6 inhibition. Combination therapies are likely required for the effective treatment of disease, and drug screening demonstrated additive/antagonistic interactions with CDK4/6 inhibitors. Agents dependent on mitotic progression (taxanes/PLK1 inhibitors) were antagonized by CDK4/6 inhibition, while the response to 5-FU and gemcitabine exhibited drug specific interactions. PI3K/MTOR and MEK inhibitors potently cooperated with CDK4/6 inhibition. These agents were synergistic with CDK4/6 inhibition, blocked the aberrant upregulation of Cyclin E1, and yielded potent inhibition of tumor cell growth. Together, these data identify novel mechanisms of resistance to CDK4/6 inhibitions and provide a roadmap for combination therapies in the treatment of PDA.